A review of the diagnosis and management of pediatric psychodermatologic conditions: Part II. Issue 1 (29th December 2021) - Mosca, Megan; Martin, Kari; Hong, Julie; Hadeler, Edward; Brownstone, Nicholas; Koo, John
Abstract: Pediatric psychodermatologic conditions encompass both primary dermatologic conditions with psychiatric comorbidities and primary psychiatric conditions with self‐induced dermatologic manifestations. Detection, diagnosis, and management of primary psychiatric conditions with dermatologic manifestations are challenging due to patient‐perceived stigma and lack of educational opportunities for dermatology providers. This two‐part series highlights the most up‐to‐date evidence‐based data and management techniques of some of the more common dermatoses of primary psychiatric conditions in children. Part I includes trichotillomania, skin picking disorder, and onychophagia, and part II covers dermatitis artefacta, body dysmorphic disorder, and delusions of parasitosis by proxy, with special considerations for family dynamics.